Indonesian high school students’ attitudes towards varieties of English: A survey study - Ruth Eliana Franssisca; Adaninggar Septi Subekti (Studies in English Language and Education, 2022)
The present study was conducted to investigate Indonesian High School students’ attitudes towards World Englishes, a construct developed based on a three-circle model proposed by Kachru. The study used an online questionnaire consisting of 22 items. The number of high school students from various regions in Indonesia participating in the study was 121. It was found that there was a moderate level of acceptance towards varieties of English. The participants believed that they should learn and be taught English varieties from inner-circle countries. However, the participants seemed to have very strong beliefs towards and pride in their local accents, to have high respect towards various accents around the world, and to perceive English to belong to whoever speaks it. Based on the finding on the participants’ positive attitude towards their local accents, English instruction could focus on the eventual purpose of learning a language, which is communication and building positive students’ self-perception about themselves regarding English. Hence, instead of comparing themselves with native speakers of English, students could focus on sharpening their English skills regardless of accents to be a part of the global community. The limitations and contributions of the present study are also presented, along with possible directions for relevant future studies in the field.